FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN ELEKTRIKAL PADA PEKERJA ELEKTRIK: LITERATURE REVIEW - Bintang Dwi Putro; Doni Hikmat Ramdhan (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Electrical accidents have a direct impact on workers' health conditions, production losses and losses experienced by companies due to loss of assets when work accidents occur. Accidents that occur are caused by several factors, which by knowing these factors, can provide relevant information regarding the causes of the occurrence of an electrical accident so that workers can prevent it before it happens. The research was carried out using the "PRISMA" method or (preferred reporting items for systematic reviews and meta-analyses). In searching for relevant research using database google scholar and Sciendirect, with keywords “Electrical accident” And “Electrician Workers”. The total number of journals that meet the inclusion and exclusion criteria is 6 journals, consisting of 2 journals indexed Q1, 1 journal indexed Q2 and 3 journals indexed Q3. The research results stated that there were 2 factors related to electrical accident that is safety climate factor (safety participation, safety compliance, safety training, safety knowledge, safety motivation, working environment, work procedure) And personal factor (personal stress, fatigue, social support, job stress, self extreme. So, it can be concluded that the factors related to electrical accidents are safety climate factors And personal factors.